Correlation between corrected serum calcium and serum albumin in children with idiopathic nephrotic syndrome in North central, Nigeria - Aliyu, Ozohu A.; Mohammed, Shamsudeen; Abdullahi, Yakubu (International Journal of Contemporary Pediatrics, 2021)
Background: Nephrotic syndrome is a clinical condition caused by alteration of glomerular membrane permeability resulting in a net loss of protein, and vitamin D binding proteins in urine leading to hypoalbuminaemia and hypocalcaemia. A positive correlation between serum albumin and ionized calcium in childhood nephrotic syndrome has been described but the correlation between total serum calcium or corrected serum calcium and serum albumin has not been extensively described. Methods: This study was carried out at Dalhatu Araf Specialist Hospital, Lafia Nigeria. Fifteen children with idiopathic nephrotic syndrome were recruited consecutively as the cases, 15 age and gender matched healthy children were recruited as the controls. Total serum calcium and albumin was assayed in all these children. Corrected serum calcium was calculated for the cases. Tests of correlation was carried out to see if there was any relationship between corrected or total serum calcium and serum albumin. Results: The mean total serum calcium and serum corrected calcium levels in the cases was 2.04±0.34 mmol/l and 2.5 mmol/l respectively. The mean total serum calcium was 2.12±0.32 mmol/l for the controls. The mean serum albumin level was 14.7±4.1 g/l and 34.6±2.7 mmol/l for the cases and controls respectively. A negative and weak correlation was found between serum albumin and corrected serum calcium and a similar negative correlation between serum albumin and total serum calcium. Conclusions: The common reports of a positive correlation between serum ionized calcium and serum albumin cannot be applied to total or corrected serum calcium and serum albumin.